Re-irradiation for recurrent high-grade gliomas: a systematic review and analysis of treatment technique with respect to survival and risk of radionecrosis. Issue 2 (14th June 2018) - Shanker, Mihir; Chua, Benjamin; Bettington, Catherine; Foote, Matthew C; Pinkham, Mark B
Abstract: Background: Re-irradiation may be considered for select patients with recurrent high-grade glioma. Treatment techniques include conformal radiotherapy employing conventional fractionation, hypofractionated stereotactic radiotherapy (FSRT), and single-fraction stereotactic radiosurgery (SRS). Methods: A pooled, population-weighted, multiple linear regression analysis of publications from 1992 to 2016 was performed to evaluate the relationships between re-irradiation technique and median overall survival (OS) and radionecrosis outcomes. Results: Seventy published articles were analyzed, yielding a total of 3302 patients. Across all studies, initial treatment was external beam radiotherapy to a median dose of 60 Gy in 30 fractions, with or without concurrent chemotherapy. On multivariate analysis, there was a significant correlation between OS and radiotherapy technique after adjusting for age, re-irradiation biologically equivalent dose (EQD2), interval between initial and repeat radiotherapy, and treatment volume ( P < .0001). Adjusted mean OS was 12.2 months (95% CI, 11.8–12.5) after SRS, 10.1 months (95% CI, 9.7–10.5) after FSRT, and 8.9 months (95% CI, 8.4–9.4) after conventional fractionation. There was also a significant association between radionecrosis and treatment technique after adjusting for age, re-irradiation EQD2, interval, and volume ( P < .0001). Radionecrosis rate was 7.1% (95% CI, 6.6–7.7) after FSRT, 6.1% (95% CI, 5.6–6.6) after SRS, and 1.1% (95% CI, 0.5–1.7) after conventional fractionation. Conclusions: The published literature suggests that OS is highest after re-irradiation using SRS, followed by FSRT and conventionally fractionated radiotherapy. Whether this represents superiority of the treatment technique or an uncontrolled selection bias is uncertain. The risk of radionecrosis was low for all modalities overall. Re-irradiation is a feasible option in appropriately selected patients.